FACING BITTER TRUTH OF BONES. ASSESSMENT OF OSTEOPOROSIS KNOWLEDGE AND BELIEFS IN COMMUNITY SETTINGS - YUSRA HABIB KHAN; AZMI SARRIF; AMIR HAYAR KHAN (International Journal of Pharma and Bio Sciences, 2013)
Osteoporosis is a metabolic disease that has emerged as a major public health concern due to its delayed diagnosis, lifelong treatment and complicated outcomes. Until now, osteoporosis is still being neglected either considering it as a fated part of aging or disease of the elderly. This neglecting behavior is due to low awareness and low knowledge of disease among the general population. The aim of the study was to evaluate existing knowledge, attitude and practices of multi-ethnic Malaysian population towards osteoporosis and to study the relationship between significant demographic factors and knowledge of the disease. Based on results of study, ethnicity, education and prior diagnosis of any bone disease were the most significant demographic factors that influence knowledge, attitude and practices. Awareness campaigns based on health belief model should be designed and implemented for multi-ethnic Malaysian population.